A new approach to the study of atomic structure and quantum numbers - Badalboyeva Dilorom Sobirjon qizi; Aliyeva Mushtari Zaylobidin qizi (International Journal on Orange Technologies, 2020)
This article deals with the main fields of study in chemistry: the atom, atomic structure, and quantum numbers. The article also discusses teaching methods in the above areas.